2006
DOI: 10.1016/s1130-1473(06)70354-2
|View full text |Cite
|
Sign up to set email alerts
|

Artrodesis cervical anterior mediante implante de tantalio. Resultados clínicos y radiológicos

Abstract: Anterior cervical discectomy and interbody fusion (ACDF) is a widely accepted surgical technique in the treatment of cervical disc disease. Tantalum cages have been recently introduced in spine surgery for interbody fusion because of the advantages of their mechanical properties. We present the results of a prospective clinical and radiological study on 24 consecutive patients who underwent an ACDF with tantalum cages. Clinical evaluation was assessed preoperatively and after surgery by a questionnaire that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“… 22 25 Moreover, clinical studies also reported that symptomatic disc degeneration at the adjacent levels were due to ACDF. 26 , 27 Theoretically, intact segments will compensate for the motion loss of the fused levels to attempt to maintain the total ROM after ACDF. 23 Therefore, multilevel fusion will cause a compensatory increase of the motion at the adjacent levels, which will lead to ASD consequently in long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“… 22 25 Moreover, clinical studies also reported that symptomatic disc degeneration at the adjacent levels were due to ACDF. 26 , 27 Theoretically, intact segments will compensate for the motion loss of the fused levels to attempt to maintain the total ROM after ACDF. 23 Therefore, multilevel fusion will cause a compensatory increase of the motion at the adjacent levels, which will lead to ASD consequently in long-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…ACDF, a safe and reliable technique, is regarded as the gold standard procedure for single or multilevel cervical spondylosis leading to radiculopathy and/or myelopathy6,8,22,23). However, fusion can lead to a loss of ROM and increase of load to adjacent levels, which may accelerate degeneration in adjacent segments.…”
Section: Discussionmentioning
confidence: 99%
“…C-TDR is also believed to reduce the incidence of ASD. Robertson et al reported that maintaining motion rather than fusion will delay or prevent symptomatic postoperative disc disease and will decrease to a significant degree the associated adjacent-level radiological disc disease23). Although, there is a considerable body of literature regarding the outcome of single level C-TDR, multilevel cervical TDR has not been comprehensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…[36] The selection of optimal surgical treatment for CSM, especially for multilevel cervical spondylotic myelopathy (mCSM), remains controversial. [19] Surgeries mainly involved anterior and posterior approaches, including anterior cervical discectomy and fusion (ACDF), [1012] anterior cervical corpectomy and fusion (ACCF), [1115] laminoplasty, [1620] laminectomy, [12,1822] and laminectomy with fusion. [2023] ACDF for treating CSM was firstly introduced by Smith and Robinson [24] and Cloward [25] ; the anterior procedure has become the most widely used surgical choice.…”
Section: Introductionmentioning
confidence: 99%